Adult Basic Education. Southeast Florida Training Center for Adult Literacy Educators Conference Proceedings (Miami, Florida, June 8, 1990) Blanca R. Polo, Comp. - Polo, Blanca R. (Distributed by ERIC Clearinghouse, 1990)
Adult education is an umbrella concept under which come various dimensions, including adult literacy, adult basic education, continued education, continued professional education, and adult vocational education. To be effective, an adult educator must realize that: (1) adults learn differently than children do; (2) adult education must develop self-directed independent learners; (3) adults want to be challenged; and (4) adult educators must be critical of themselves. Certain basic principles are involved in developing effective strategies and techniques in the classroom. They are: participation, respect for self-worth, collaboration, practice, critical principles input or critical reflection, and self-directed learning. Adult educators should prioritize these six principles with respect to their practice. As instructors working with learning disabled adults, educators should realize there are problems and deal with them; know what methods are available to deal with them; implement them; and have a plan of action to get learners through learning barriers. (YLB)